2005
DOI: 10.1161/01.res.0000191538.76771.66
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Transforming Growth Factor-β Signaling in Endothelial Cells

Abstract: Abstract-Many forms of vascular disease are characterized by increased transforming growth factor (TGF)-␤ 1 expression and endothelial dysfunction. Smad proteins are a key step in TGF-␤-initiated signal transduction. We hypothesized that NO may regulate endothelial TGF-␤-dependent gene expression. We show that NO inhibits TGF-␤/Smad-regulated gene transactivation in a cGMP-dependent manner. NO effects were mimicked by a soluble analogue of cGMP. Inhibition of cGMP-dependent protein kinase 1 (PKG-1) or overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 56 publications
11
84
2
1
Order By: Relevance
“…12,33,37,38 This assumption is based on the known inhibitory effects of cGMP on collagen synthesis and the TGFb1 pathway, and its vasculoprotective effects on arterial SMC. [14][15][16][17]20,[45][46][47] However, the anti-apoptotic and pro-proliferative effects of sildenafil that we found in the corporal smooth muscle do not agree with the fact that cGMP inhibits vascular SMC proliferation. 48,49 Since the effects of BCNR on the corporal histology and pharmacokinetics are the same as those seen in the aged rat, we assume that cGMP effects on corporal SMC may be modulated by some specific features in the corporal SMC themselves or the tissue milieu, that are not operative in the vascular SMC.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…12,33,37,38 This assumption is based on the known inhibitory effects of cGMP on collagen synthesis and the TGFb1 pathway, and its vasculoprotective effects on arterial SMC. [14][15][16][17]20,[45][46][47] However, the anti-apoptotic and pro-proliferative effects of sildenafil that we found in the corporal smooth muscle do not agree with the fact that cGMP inhibits vascular SMC proliferation. 48,49 Since the effects of BCNR on the corporal histology and pharmacokinetics are the same as those seen in the aged rat, we assume that cGMP effects on corporal SMC may be modulated by some specific features in the corporal SMC themselves or the tissue milieu, that are not operative in the vascular SMC.…”
Section: Discussioncontrasting
confidence: 91%
“…[11][12][13] It is likely that this occurs through the maintenance of high levels of cGMP, since this compound reduces collagen synthesis and the activation of the pro-fibrotic TGFb1 pathway and protects SMC from apoptosis, while stimulating the spontaneous induction of inducible nitric oxide synthase (iNOS, also known as NOS2). [14][15][16][17][18][19][20][21][22][23] The expression of iNOS in certain non-immunological tissues is assumed to be a defense mechanism against fibrosis. [24][25][26][27][28][29] The nitric oxide produced by iNOS, besides inhibiting collagen synthesis and the TGFb1 pathway, also quenches reactive oxygen species, and in some cases, the differentiation of fibroblasts to myofibroblasts, the cells that produce collagen in many fibrotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TGF-β1 upregulates PAI-1 expression at the transcriptional level via the TGF-β1/SMADs and TGF-β1/MAPK signaling pathways (27,28). PAI is a serine protease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have showed that ROS can regulate TGF-β1 synthesis GONZÁLEZ-RAMOS ET AL. 4 (5,12,17,23,25,32) also through the activation of the transcription factor AP-1 (12). Taking into account this fact, we hypothesized that basal concentrations of ROS could be involved in the constitutive expression of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%